(untitled) (IMC Journal of Medical Science, 2018)
Background and objectives: Acute pancreatitis is a common condition for hospital admission. In Bangladesh, no study has yet investigated the clinical profile, degree of severity and underlying factors of acute pancreatitis. The aim of the present study was to determine the clinical profile, degree of severity and underlying factors of acute pancreatitis in a cohort of Bangladeshi patients. Methods: This prospective study was conducted from April 2016 to March 2017 on patients admitted with acute pancreatitis at Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) General Hospital, Dhaka, Bangladesh. History and clinical features of each patient was systematically recorded. Diagnosis of acute pancreatitis was made by clinical findings, serum amylase and lipase levels (> 3 times the upper limit of normal values), evidences of acute pancreatitis by ultrasonography and computed tomography (CT). Severity of acute pancreatitis was classified according to the revised version of Atlanta classification. Results: A total of 40 patients with acute pancreatitis were enrolled in the study. Male and female were equally distributed. The mean age was 44.3±2.7 years. Among 40 cases, 26 (65.0%) and 14 (35%) had moderate and severe acute pancreatitis respectively. No specific clinical feature including ascites or pleural effusion was found significantly related to severity of the disease. Gall stone and metabolic (hypertriglyceridaemia/hypercalcemia) causes were present in 62.5% cases, but none had significant association with the severity of the disease. Conclusion: The present study has demonstrated that no specific observed clinical feature or underlying factor was related to the degree of severity of acute pancreatitis in a cohort of Bangladeshi patients. IMC J Med Sci 2018; 12(1): 6-10